Associations between neighborhood socioeconomic environment and physical activity in Cuban immigrants - Olivia Affuso; Chelsea R. Singleton; Scott C. Brown; Tatiana Perrino; Shi Huang; José Szapocznik (SSM: Population Health, 2016)
Physical inactivity is a major public health concern because it is a determinant of obesity and obesity-related chronic diseases. Few longitudinal studies have examined the association between neighborhood socioeconomic (SES) environment and change in physical activity behaviors. Additionally, few studies have examined this association in immigrant groups or Hispanic subgroups such as Cubans. This research aimed to determine if neighborhood SES is associated with longitudinal change in moderate-to-vigorous physical activity (MVPA) among Cuban immigrants who participate in the Cuban Health Study in Miami, Florida. Data on 280 participants [mean age: 37.4 (±4.6), 48.9% women, mean body mass index: 25.0 (±2.5)] collected at baseline, 12 months and 24 months were analyzed. Minutes of MVPA were objectively measured during each data collection period using accelerometers. A neighborhood SES score was calculated for each participant’s residential census tract from American Community Survey data on median household income, median housing value, educational attainment and occupation. The neighborhood SES score was grouped into tertiles, reflecting low, moderate and high neighborhood SES environment. Multilevel linear models were used to examine the relationship between neighborhood SES and change in MVPA over 24 months. At baseline, 94 (33.6%), 108 (38.6%) and 78 (27.9%) participants resided in low, moderate, and high SES neighborhoods, respectively. After adjusting for age, sex, and body mass index, no difference in average change in MVPA over time was observed between participants residing in low and moderate SES neighborhoods (p=0.48) or low and high SES neighborhoods (p=0.62). In Cuban immigrants, longitudinal change in MVPA may not vary by neighborhood socioeconomic environment. Keywords: Neighborhood, Environment, Socioeconomic status, Physical activity, Cuban, Immigrant